The bravest dog ever : the true story of Balto - Standiford, Natalie (New York : Random House, 1989)
Recounts the life of Balto, the sled dog who saved Nome, Alaska in 1925 from diptheria epidemic be delivering medicine through a raging snowstorm.
Keywords: Balto (Dog) -- Juvenile literature; Sled dogs -- Alaska -- Nome -- Biography; Diptheria -- Alaska -- Nome -- Prevention